Answer:
![f(x)=x^2+3x+2](https://img.qammunity.org/2021/formulas/mathematics/high-school/sv3qh38w1frjaug9pyq7zl3kao9c616qdu.png)
Explanation:
We want to write the equation of a quadratic whose graph passes through (-3, 2), (-1, 0), and (1, 6).
Remember that the standard quadratic function is given by:
![f(x)=ax^2+bx+c](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hj2cyo9lipsf2imfe8tb04vftddbodxbcu.png)
Since it passes through the point (-3, 2). This means that when
,
. Hence:
![f(-3)=2=a(-3)^2+b(-3)+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/z7w2cds5rl1ab4szck5s0oq5zmu49nvln0.png)
Simplify:
![2=9a-3b+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/d4hfw07ufk26a2tr945lr0yp4wa6237uxz.png)
Perform the same computations for the coordinates (-1, 0) and (1, 6). Therefore:
![0=a(-1)^2+b(-1)+c \\ \\0=a-b+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/ht81x4mtsevdsk1r5h9311zwpsz1f82h8e.png)
And for (1, 6):
![6=a(1)^2+b(1)+c\\\\ 6=a+b+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/q4jo2zw6st17cpiy30gg8rydivmzk1rzqn.png)
So, we have a triple system of equations:
![\left\{ \begin{array}{ll} 2=9a-3b+c &\\ 0=a-b+c \\6=a+b+c \end{array} \right.](https://img.qammunity.org/2021/formulas/mathematics/high-school/kq34h7wyq4heqo6umu9f98z1g1mohhc8j3.png)
We can solve this using elimination.
Notice that the b term in Equation 2 and 3 are opposites. Hence, let's add them together. This yields:
![(0+6)=(a+a)+(-b+b)+(c+c)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ubbtnfm2y1g8idolftf6fo3dn9trwowcey.png)
Compute:
![6=2a+2c](https://img.qammunity.org/2021/formulas/mathematics/high-school/ww3nrzoch9anuzx55hc33ii1hqsd2whjgq.png)
Let's divide both sides by 2:
![3=a+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/oys9uuxely82pmm3w6i201eaizbxtlt9rl.png)
Now, let's eliminate b again but we will use Equation 1 and 2.
Notice that if we multiply Equation 2 by -3, then the b terms will be opposites. So:
![-3(0)=-3(a-b+c)](https://img.qammunity.org/2021/formulas/mathematics/high-school/obzj2dqxvkkrwasvwwewoejl2csxmpzoy1.png)
Multiply:
![0=-3a+3b-3c](https://img.qammunity.org/2021/formulas/mathematics/high-school/y89vzlv462p2b489qynzkpguse64o8ke27.png)
Add this to Equation 1:
![(0+2)=(9a-3a)+(-3b+3b)+(c-3c)](https://img.qammunity.org/2021/formulas/mathematics/high-school/8ktd7xy9epcguja4t196tuv2frs4vtngv9.png)
Compute:
![2=6a-2c](https://img.qammunity.org/2021/formulas/mathematics/high-school/o3r79547blohlxvhc70l217or6ptpo0j6w.png)
Again, we can divide both sides by 2:
![1=3a-c](https://img.qammunity.org/2021/formulas/mathematics/high-school/hp6rmw9113dnseqhw33ms0p2ebd4nbwh94.png)
So, we know have two equations with only two variables:
![3=a+c\text{ and } 1=3a-c](https://img.qammunity.org/2021/formulas/mathematics/high-school/m9iuq3njp3nqd4uzlbdg8coe6oi0lrsqfu.png)
We can solve for a using elimination since the c term are opposites of each other. Add the two equations together:
![(3+1)=(a+3a)+(c-c)](https://img.qammunity.org/2021/formulas/mathematics/high-school/wfy1sd2quj9f4w1orqiirhwzj835wr8yto.png)
Compute:
![4=4a](https://img.qammunity.org/2021/formulas/mathematics/high-school/o26e5quufbn3mgh3fxb9r7lx7ca4c6t208.png)
Solve for a:
![a=1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5oxpt0qyc43lnwntseh2gtnbwlxpyz6p09.png)
So, the value of a is 1.
Using either of the two equations, we can now find c. Let's use the first one. Hence:
![3=a+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/oys9uuxely82pmm3w6i201eaizbxtlt9rl.png)
Substitute 1 for a and solve for c:
![\begin{aligned} c+(1)&=3 \\c&=2 \end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/high-school/7i3a8fqnc4cj2xmu14enfmvr7k20xxgbxl.png)
So, the value of c is 2.
Finally, using any of the three original equations, solve for b:
We can use Equation 3. Hence:
![6=a+b+c](https://img.qammunity.org/2021/formulas/mathematics/high-school/1etqe6nv6a278i7ahs2nhkvov9bp2h8nxz.png)
Substitute in known values and solve for b:
![6=(1)+b+(2)\\\\6=3+b\\\\b=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/w71ufd9ekcmpwhrgq13ab4vyiur0rsca9n.png)
Therefore, a=1, b=3, and c=2.
Hence, our quadratic function is:
![f(x)=x^2+3x+2](https://img.qammunity.org/2021/formulas/mathematics/high-school/sv3qh38w1frjaug9pyq7zl3kao9c616qdu.png)